Inverted OPVs with MoS2 hole transport layer deposited by spray coating. (September 2017) - Barrera, Diego; Jawaid, Ali; Daunis, Trey B.; Cheng, Lanxia; Wang, Qingxiao; Lee, Yun-Ju; Kim, Moon J.; Kim, Jiyoung; Vaia, Richard A.; Hsu, Julia W.P.
Abstract: Molybdenum disulphide (MoS2 ) exhibits high work function and high mobility, making it a promising candidate for electronic applications. Currently, most applications require high vacuum or high reaction temperature processes to deposit MoS2 . Here, we report organic photovoltaic devices made by room-temperature spray-coating of liquid-exfoliated MoS2 suspension to form hole transport layer (HTL) on top of poly(3-hexylthiophene):phenyl-C60-butyric acid methyl ester bulk heterojunction. Such an approach is compatible with large area applications. Current-voltage data showed that fill factor of devices with MoS2 HTL is similar to the devices using poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) HTL. However, open circuit voltage and short circuit current density ( J sc ) are reduced, with the amount of J sc reduction depending strongly on active layer thickness. These results can be understood by the strong absorption of light by MoS2, reducing/eliminating the back reflection from the top silver electrode. The experimental results are corroborated by calculations using transfer matrix method. Graphical abstract: Highlights: Incorporation of MoS2 as HTL is possible without oxidizing or modifying its structural arrangement to octahedral phase. Electrical measurements on the devices showed that FF achieved using MoS2 is identical to that using spin-coated PEDOT:PSS. Low J sc in MoS2 devices is explained by lower absorption in the active layer originated by less back-reflected light.